FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI DI PUSKESMAS KALIBAWANG KULON PROGO - Prasetya Wibowo, Dika; Istianah, Umi; Adinugraha, Tetra Saktika (Jurnal Media Ilmu Kesehatan, 2015)
Background: Hypertension is a condition when artery blood pressure increases. Hypertension is also called a silent killer because in most cases it does  not  show  any  symptoms but patient is at risk of death. The  risk faktors of hypertension include both control and uncontrollable. The. Uncontrollable faktors are age, gender, and genetic faktors whereas the controllable are life styles including salt consumption, exercise, smoking habit, and obesity. Objective: to identify faktors related to hypertension in Kalibawang health center, Kulon Progo. Methods: A descriptive correlative studi at Kalibawang Community Health Center in Kulon Progo District of Yogyakakarta with a total sample of 66 respondents was applied in  this research. The  blood pressure were assess by using sphymomanometer whereas the risk faktors were gathered by using questionnaires and then analyzed by using Kendall Tau statistic with the level of significance of 90%. Results: Statistical analysis showed that salt consumption (r=0.388, p< ?), smoking habit (r= -0.240, p<?), obesity (r= -0.513, p<?), exercise (r= -.258, p<?), and genetic faktors (r=0,258, p<? ) are related to hypertension, whilst sex (r=0,190, p>?) and age (r= -0.059, p>?) were not related to hypertension. Conclusion: There is a relationship between salt consumption, smoking habit, obesity, exercise  and genetic with the incidence of hypertension in Kalibawang Community Health Center. Keywords: Hypertension, faktors of hypertension